The Hikayat Muhammad Hanafiyyah - Brakel, L. F. author. aut Link
IX, 319 p. 1 illus.
Keywords: 'If not now, when?' Hillel, Pirke Avot, I 14. The text edition which I hereby submit to the reader has been my constant companion for much of the last nine odd years. But the relative stability of my main preoccupation contrasted sharply with my wanderings during this same span of time. In fact, for most of it I was more or less constantly on the move, trekking from the Nether lands to Australia and back again, then to the United States, with three excursioru; to Indonesia. On all these trips I carried my notes and kept working on this project, the conclusion of which continued to elude me. Even today I can hardly believe it is allover - and in fact it is not, as this volume will soon be followed by a companion containing a shortened English translation and dealing in much greater detail with the relationship between the Malay Hikayat Muhammad Hanafiyyah, its Persian source and Muslim literature in general. I sincerely regret that technical and financial considerations have combined to make inclusion of the apparatus criticus in this edition impossible. A limited number of copies of this apparatus are avail able on personal application either direct from the author (C/o the Indonesian Department, Monash University, Clayton, Victoria 3168, Australia), or from the Koninklijk Instituut voor Taal-, Land- en Volkenkunde, Stationsplein 10, Leiden, the Netherlands.